Sensitivity of Acehnese varieties of rice (Oryza sativa L.) to high temperature stress during flowering stage - Sabaruddin Zakaria; . Bakhtiar; . Efendi (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
. Rice is very sensitive to high temperature stress at the flowering stage. The rice plants were exposed to high temperature condition under green house. Some varieties show tolerance to heat stress, and the others are sensitive. Nine local Acehness varieties: Si Puteh, Itam Tangke Lango, Ramos Tihion Tamping, Sireundeun Semantok, Bo Santeut Seumantok, Pade Cut Krusek, Sipirok, Sigeudop and Cantek Lembayung were observed for high temperature stress during flowering stage. The objective of this research are: to identify the effect of heat stress on reproductive stage of local Acehnese, Indonesian rice; and to find the varieties that sensitive and hopefully have the gene of “temperature genic male sterility” (TGMS) that can be used as restorer varieties for production of hybrid rice. Heat stress significantly decreased pollen viability, plant architecture, and yield components. The pollen viability was observed by stainability and germination rate of the pollen. Based on pollen germination ability showed that one variety of rice, Sigeudop, showed tolerance to high temperature stress. Whereas the sensitive variety was Bo Santeut Seumantok, the local Indonesian rice that is potential to have TGMS gene. Pollen stainability showed that all varieties of pollen involved stainability from plants cultivation at high temperature, and all the varieties had the high rate of pollen stainability. We also found that pollen germination rate showed three varieties of rice cultivated in high temperature involved high resistance of the pollens.